2021
DOI: 10.2478/bjdm-2021-0012
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cells in head and neck squamous cell carcinoma: Treatment modalities

Abstract: Summary Head and neck squamous cell carcinoma (HNSCC) belongs to the most frequent cancer subtypes in the world. Mutations due to genetic and chromosomal instability, syndromes such as Fanconi anemia and the Bloom syndrome, environmental risk factors such as tobacco smoking, alcohol and human papillomavirus infection (HPV) subtypes 16,18,31,33,35,52,58 are implicated in its pathogenesis. The HNSCC belongs to the solid tumors of epithelial origin and consists of stromal, inflammatory, cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(25 citation statements)
references
References 42 publications
(78 reference statements)
0
19
0
Order By: Relevance
“…They are responsible for the invasion and metastasis of cancer, as well as the development of chemotherapy and radiotherapy resistance. Targeting them successfully is therefore an important therapeutic goal and may be achieved by identifying specific biomarkers that are expressed by them [5]. The most frequently used CSC markers for head and neck squamous cell carcinoma are summarized in Table 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are responsible for the invasion and metastasis of cancer, as well as the development of chemotherapy and radiotherapy resistance. Targeting them successfully is therefore an important therapeutic goal and may be achieved by identifying specific biomarkers that are expressed by them [5]. The most frequently used CSC markers for head and neck squamous cell carcinoma are summarized in Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…They are responsible for the phenomena of cancer invasion and metastasis, as well as the development of resistance to chemotherapy and radiotherapy. Targeting them successfully is therefore an important therapeutic goal and may be achieved by identifying specific antigens that are expressed by them [5]. Additionally, cancer stem cells are present both in potentially malignant lesions and in cancerous lesions, most probably intervening and mediating in the process of carcinogenesis [6].…”
Section: Introductionmentioning
confidence: 99%
“…A few years later, CSC populations were also found in solid tumors [ 76 , 77 ]. Afterward, CSCs have been widely investigated and identified in various types of solid tumors, including HNC, but their role has not been fully described [ 6 , 7 , 76 , 78 ]. Several investigators showed that putative CSCs could be isolated from HNSCC tissue by their unique surface biomarker pattern expression [ 7 , 73 , 76 , 79 ].…”
Section: Cscs In Head and Neck Cancermentioning
confidence: 99%
“…Fluorescence-activated cell sorting (FACS) and magnetic-activated cell sorting (MACS) were the first techniques used for CSC separation, which allow multi-biomarker sorting of stem cells at the same time with high purity and strong specificity [ 80 , 84 ]. Other methods used for CSC separation from tumors are based on cell culture with Hoechst 33342 or the colony-forming ability of CSCs [ 7 , 24 , 78 ]. So far, multiple markers, independently or in combination, have been documented by many authors as putative CSC markers in various tumors, including HNC [ 6 , 7 , 72 , 73 , 76 , 79 ].…”
Section: Cscs In Head and Neck Cancermentioning
confidence: 99%
See 1 more Smart Citation